Decoding the Digital Divide: Public Policy for Social Inclusion in the Modern Era - Merintha Suryapuspita (International Journal of Education, Vocational and Social Science, 2025)
This article explores the multidimensional nature of the digital divide and critically examines how contemporary public policy frameworks address issues of digital inequality and social exclusion. Using a qualitative literature review approach, the study synthesizes scholarly works, international policy documents, and empirical research published within the last eight years to map current trends and challenges in digital inclusion. The analysis focuses on three interrelated dimensions of the digital divide: access to digital infrastructure, digital literacy and competencies, and active digital participation. While global internet access has expanded significantly, the literature reveals persistent disparities in skills acquisition, usage quality, and the ability to derive meaningful benefits from digital technologies particularly among rural populations, the elderly, women, and persons with disabilities. The study finds that although governments frequently employ inclusive rhetoric in their digital policies, implementation often lacks participatory planning, equitable funding, and accountability mechanisms. As a result, many inclusion programs fail to reach or empower those most at risk of digital marginalization. Drawing from best practices across various regions, the article highlights innovative policy approaches such as community-driven digital hubs, intersectional equity audits, and public-private partnerships for affordable access. The study concludes by advocating for a paradigm shift in digital policy—from a narrow focus on infrastructure provision to a holistic strategy emphasizing human-centered, adaptive, and justice-oriented digital ecosystems that promote true social inclusion in the digital era.